Initial Reports of the Deep Sea Drilling Project 1972
DOI: 10.2973/dsdp.proc.14.126.1972
|View full text |Cite
|
Sign up to set email alerts
|

Cretaceous and Cenozoic Sediments from the Atlantic Ocean

Abstract: Leg 14 of the Deep Sea Drilling Project completed 9 holes; 7 were located off NW Africa, 1 in Ceara Abyssal Plain, and 1 on Demerara Rise. Quaternary and Pliocene sediments consist of nanno chalk oozes and brown clay. The facies boundary (CCD) is near 5000 meters. Sedimentation rates are between 10 and 30 meters/million years (m/My) for chalk ooze and 2 to 4 m/My for pelagic clay. Redeposition off the Amazon produces terrigenous and bioclastic turbidite sequences with rates increasing, on the average, from 50 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

10
198
2
1

Year Published

1978
1978
2020
2020

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 156 publications
(211 citation statements)
references
References 30 publications
(45 reference statements)
10
198
2
1
Order By: Relevance
“…It seems probable that most of the "quartz" is chalcedony that has been diagenetically transformed from original biogenic opal via an intermediate stage of disordered cristobalite. This inference agrees with studies by Berger and von Rad (1972), who found that with increasing depth and age, opal and lussatite (disordered cristoba¬ lite) are finally transformed into quartzitic rock (see also Riech and von Rad, this volume).…”
Section: Unit 6 -Dark Greenish Gray and Black Claystone Withsupporting
confidence: 81%
“…It seems probable that most of the "quartz" is chalcedony that has been diagenetically transformed from original biogenic opal via an intermediate stage of disordered cristobalite. This inference agrees with studies by Berger and von Rad (1972), who found that with increasing depth and age, opal and lussatite (disordered cristoba¬ lite) are finally transformed into quartzitic rock (see also Riech and von Rad, this volume).…”
Section: Unit 6 -Dark Greenish Gray and Black Claystone Withsupporting
confidence: 81%
“…The seven sites cover a wide climatic range between the humid northern tropical belt in the south (Site 367: 12°30'N) and the humid Mediterranean belt in the north (Site 135: 35°1O'N, Site 370: 32°50'N). This distribution was shifted some 6° to 7° of latitude southward in the early Miocene, according to the reconstructions of plate motions (Francheteau, 1970;Berger and von Rad, 1972).…”
Section: Generalmentioning
confidence: 99%
“…The DSDP Leg 14 sites are discussed by Berger and von Rad (1972). Neogene to Oligocene quartzose sand layers exist in Cores 135-SW1 and SW2, 138-1 and 2, 139-6 and 7, and 140A-1 and 2.…”
Section: Sites 135 and 138 139 140 (Leg 14)mentioning
confidence: 99%
See 2 more Smart Citations